Systematic review and meta-analysis of type B aortic dissection involving the left subclavian artery with a Castor stent graft - Yao, Shihua; Chen, Xu; Liao, Yalin; Ding, Gangbing; Li, Dagang; Qin, Gengliang; Qiao, Ruiguo; Sun, Xin; Zheng, Qijun (Frontiers in Cardiovascular Medicine, 2022)
Objective Despite the rapid development of thoracic endovascular aortic repair (TEVAR), it is still a challenge to maintain the blood flow of the branch arteries above the aortic arch in Stanford type B aortic dissection involving the left subclavian artery (LSA). The Castor stent graft is an integrated, customized, single-branch stent that enables reconstruction of the LSA. The purpose of this systematic review and meta-analysis was to assess the efficacy of the Castor stent graft for type B aortic dissection. Materials and methods An extensive electronic literature search (PROSPERO registration number: CRD42022322146) was undertaken to identify all articles published up to August 2022 that described thoracic aortic repair with branch stents in the treatment of type B aortic dissection involving the LSA. The quality of the included studies was analyzed using the MINORS criteria. The primary outcome measures were the technical success rate, early mortality rate, endoleak rate, and 1-year survival rate. The secondary outcome measures were the stroke rate, left upper extremity ischemia rate, and target vessel patency rate. Results Eleven studies involving 415 patients were eligible for this meta-analysis. The LSA was successfully preserved in all procedures. The technical success rate was 97.5% (95% CI: 0.953–0.991); the intraoperative endoleak rate was 0.1% (95% CI: 0.000–0.012); the intraoperative LSA patency rate was 99.52%; the intraoperative LSA stent deformation and stenosis rate was 0.15% (95% CI: 0.000–0.051); the early type I endoleak rate was 1.6% (95% CI: 0.003–0.035); the 30-day mortality rate was 0.96%; the early reintervention rate was 0.9% (95% CI: 0.000–0.040); and the perioperative stroke rate was 0% (95% CI: 0.000–0.005). The 1-year survival rate was 99.7% (95% CI: 0.976–1.000). The half-year LSA patency rate was 99.3%, the 1-year LSA patency rate was 97.58%, and the 2-year LSA patency rate was 95.23%. During the follow-up period, the leakage rate was 0.3% (95% CI: 0.000–0.017), the incidence of left upper extremity ischemia rate was 0.5% (95% CI: 0.000–0.035), and the deformation and stenosis rate of the LSA stent was 2.2% (95% CI: 0.06–0.046). Conclusion This meta-analysis shows that endovascular repair of type B aortic dissection using the Castor stent-graft may be technically feasible and effective. However, this conclusion needs to be interpreted with caution, as the quality of evidence for all outcomes is between low and very low. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42022322146].